A Systematic Review: Software Test Case Prioritization Techniques - Sarika Chaudhary,Aman Jatain (International Journal of Advanced Science and Technology, 2020)
Advancement in information technology and increased need of real time systems results in development of highly complex and monolithic software’s. Such systems demands huge number of test suits to validate the requirements. Exhaustive testing of large test suits is not feasible due to time and cost limitations. Also it has been becoming really hard to maintain high complexity software by preserving its quality in an elegant manner. For this, software engineers have realized the need of Test Case Prioritization. It is an important approach in regression testing. Regression testing is nothing but re run of entire test suites to make sure that changes in functionality and structure of software still complies with customer requirements and Test Case Prioritization aims to reorder and execute higher priority test first than the lower priorities based on particular criteria. The idea behind this paper is to figure out the important research directions in the area of Test Case Prioritization, which necessitate further need to build effective techniques for Test Case Prioritization. This paper first discusses the state of art in regression testing and then present the review result of various prioritization techniques developed in between 2009-2019 and later outline the trends and future scope.